Dividing Housework between Partners: Individual Preferences and Social Norms - Danilo Cavapozzi; Marco Francesconi; Cheti Nicoletti (Institute of Labor Economics (IZA), 2024)
Using UK longitudinal data on dual-earner couples, this paper estimates a model of intrahousehold housework decisions, which combines a randomized experimental framework eliciting counterfactual choices with gender norms differences across ethnicities and cohorts to identify the impacts of individual preferences and gender identity norms. Equal sharing of tasks yields greater utility for both men and women, with women disliking domestic chores as much as men. Although couples would want to use housework arrangements to compensate for differentials in labor market involvement, women end up performing a substantially larger share of housework. This is not due to specialization, rather social norms play a key role. Exposure to more egalitarian gender attitudes significantly increases the probability of choosing an equal share of housework. Were attitudes evened up to the most progressive levels observed in the sample, women doing more housework than their partners would stop to be the norm already among present-day households, except for households with children.
Keywords: C25; C26; D13; J16; J22; 330; intrahousehold allocation of chores; labor supply; vignettes; gender identity norms; gender gaps